Understanding the uniqueness of the stepwise [4 + 1] cycloaddition reaction between conjugated nitroalkenes and electrophilic carbene systems with a molecular electron density theory perspective. Issue 2 (24th August 2020) - Kącka‐Zych, Agnieszka
Abstract: The [4 + 1] cycloaddition (41CA) and [2 + 1] cycloaddition (21CA) reactions of the α‐halogeno‐nitroalkenes with carbene have been studied using the molecular electron density theory through density functional theory calculations at the MPWB1K(PCM)/6‐311G(d, p) computational level. The 41CA reaction take place through a polar two‐step mechanism involving the formation of a zwitterionic intermediate. The competitive 21CA reaction path proceeds according to nonconcerted two‐stage one‐step. Bonding evolution theory analysis of 41CA reaction allows the distinguishing of four groups along the reaction path. The reaction begins with rupture of the CC double bond of the alkene moiety and formation of the pseudoradical center. Formation of the OC and CC new single bonds begins in subsequent phases. In the last stage of the 41CA reaction path, we observed the formation of an NC new double bond. In the case of 21CA reaction path, we observed the successive rupture of the CC double bond of the alkene moiety, formation of CC new single bond and pseudoradical center, and creation of a second CC single bond. Abstract : The molecular mechanism of the reaction of (E)‐1, 1, 1‐trifluoro‐3‐nitrobut‐2‐ene with 3, 3‐dimethyl‐2‐morpholinobutene has been studied within the molecular electron density theory. This theoretical study confirm the possibility of the formation of zwitterionic structures in the first reaction stage. Interestingly, that localized zwitterions are however not common intermediates for identified in the postreaction mixture products.